Clusters of galaxies in the Planck survey. Issue 4 (2nd May 2013) - Pointecouteau, E.; Schartel, Norbert
Abstract The Planck satellite has surveyed the whole sky more than four times. The nominal mission of two all‐sky surveys will be released to the public in 2013. From the first all‐sky survey, we have demonstrated the ability to detect clusters via the Sunyaev‐Zel'dovich effect with high reliability and out to large redshifts. We have released the first large sample of 189 high signal‐to‐noise SZ clusters. We also presented the detection of 45 new Planck clusters, confirmed in X‐ray with the XMM‐Newton satellite. The Planck collaboration is engaged in a massive identification and follow‐up programme of its SZ sources at X‐ray, optical, and SZ wavelengths. Dedicated cluster studies are also conducted by the consortium in order to better constrain the scaling and structural properties of the cluster population. We have thus provided high precision calibration of scaling relation between the SZ signal and the clusters physical quantities. The excellent agreement found between SZ and X‐ray measurements have demonstrated our good understanding of the hot intra‐cluster gas at least within R500. These results together with those from other operating SZ instruments are shading new light on our understanding of the most massive bound structure of the Universe. With its whole sky reach and unprecedented frequency coverage, the Planck mission is a crucial asset to these endeavours. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)